2012
DOI: 10.1016/j.lungcan.2011.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of functional capacity and exercise behavior in patients with metastatic non-small cell lung cancer

Abstract: Background To investigate the prognostic importance of functional capacity and exercise behavior in patients with metastatic non-small cell lung cancer (NSCLC). Patients and methods Using a prospective design, 118 consecutive participants with histologically confirmed metastatic (inoperable) NSCLC and Eastern Cooperative Oncology group (ECOG) 0–3 completed a six-minute walk test to assess functional capacity and questionnaire that assessed self-reported exercise behavior. Cox proportional models were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
146
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(160 citation statements)
references
References 35 publications
4
146
1
3
Order By: Relevance
“…[12][13][14] These techniques have not been studied in patients planning to undergo HCT. Studies have demonstrated the feasibility of VO 2peak measurement in survivors of allogeneic HCT, [15][16][17] and the potential benefit of exercise intervention in ameliorating functional decline.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] These techniques have not been studied in patients planning to undergo HCT. Studies have demonstrated the feasibility of VO 2peak measurement in survivors of allogeneic HCT, [15][16][17] and the potential benefit of exercise intervention in ameliorating functional decline.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer patients who are more physically able are less likely to have treatment resistant-disease 46 and to experience increased life expectancy [46][47][48] .…”
mentioning
confidence: 99%
“…Recent studies also show that physical performance is an independent predictor of survival in NSCLC patients [21][22][23], currently the same goes for depression and anxiety which usually accompanies the disease [24].…”
Section: Introductionmentioning
confidence: 89%
“…The same author has subsequently shown that the reduction in exercise capacity is a strong predictor of mortality, which is regarded as the VO 2 peak [33], or the MET'S products or meters walked to the walk test [34].…”
Section: Functional Assessmentmentioning
confidence: 99%